The Maintenance of Siladang Language - Horia Siregar; Busmin Gurning (Universitas Negeri Medan, 2016)
This study observed Siladang language maintenance in Desa Sipapaga. The objectives of the study are (1) to examine the factors affecting language maintenance (2) to find out the strategies in maintaining the Siladang language and (3) to find out the reasons of the Siladang people in maintaining their language. The method of this study was descriptive qualitative research. The participants were 20 Siladang people who live in Desa Sipapaga were taken by purposive random sampling. The research results are as follows (1) There are seven factors affecting Siladang language maintenance in Desa Sipapaga such as, Ethnolinguistic vitality, living together and see each other frequently, use of language in family domain (intra and inter marriage family, use of language in neighbor domain, use of language in religion domain, use of language in workplace domain, and practice traditional ceremony, (2) In maintaining the Siladang language, the Siladang people conducted some strategies such as; family language policy, using Siladang language in their daily life frequently, the using of Siladang language in cultural activity like in wedding ceremony. (3) The reasons of the Siladang people maintain their language are; they were proud of being Siladang people and speak Siladang language, and speak Siladang language shows their identity as Siladang people. Keywords: language maintenance, Siladang